הקדמות לחקר האוקולטיזם היהודי: הגדרות, תיחומים והשפעה - גלאובר-זמרה שמואל; הוס בעז (מחשבת ישראל, 2022)
This article presents a preliminary overview of Jewish involvement in modern occult movements and representations of occultism in Jewish culture from the late nineteenth to the mid-twentieth centuries. Jews across the world at this time took an interest in occult currents that emerged in European and North American society. This entailed both a centrifugal movement on the part of Jews toward broader occult movements, as well as a centripetal incorporation of occult trends within Jewish popular culture and religious thought: many Jews joined Western esoteric movements, while occult currents were integrated into Jewish popular culture and religious literature. Those interested in occultism and esoteric movements included leading Jewish writers, scholars, rabbis, artists, and political activists. Many Jews who took part in the esoteric milieu aspired to integrate Judaism with Western esotericism, at times yielding novel modes of modern Jewish occultism. These modern Jewish occult forms, largely forgotten today, were interwoven into numerous works of Jewish literature, art, and religious thought from the late-nineteenth to the mid-twentieth centuries, while also exerting an influence on broader alternative spiritual movements to this day. The article discusses the challenges of defining Jewish occultism and examine its scope and impact within the respective fields of Jewish studies and Western esotericism. The framework of Jewish occultism, we argue, calls into question several conventions of modern Jewish historiography. Long overlooked, the study of modern Jewish occultism stands to challenge prevailing conceptions of Jewish modernity and secularization, while offering new research paradigms for the historical study of nineteenth- and twentieth-century Judaism and Western esotericism.